Prácticas de crianza y competencia social en niños de 3 a 5 años - Pichardo Martinez, Maria del Carmen (2022)
Social competence is one of the most important skills for the adequate personal adjustment to society. The family becomes the first and most important childhood socializing agent because during this period children learn social skills, attitudes and other skills necessary for adapting themselves to the context in which they are living. The purpose of this paper is to establish the relationship between parents’ rearing styles and children’s social competence. In the study, 206 students from 3 to 5 years old and their parents were involved. Results show that parental supervision is one of the characteristics of rearing styles that has the most positive effects on children’s social competence. On the contrary, other rearing practices such as the use of punishment or negative expression of affection are related with maladjusted behaviors.